Diagnosis of GH Deficiency Without GH Stimulation Tests - Ibba, Anastasia; Loche, Sandro (Frontiers in Endocrinology, 2022)
Growth hormone deficiency (GHD) is the most commonly affected pituitary hormone in childhood with a prevalence of 1 in 4000–10000 live births. GH stimulation testing (GHST) is commonly used in the diagnostic workup of GHD. However, GHD can be diagnosed in some clinical conditions without the need of GHST. The diagnosis of GHD in newborns does not require stimulation testing. Likewise infants/children with delayed growth and/or short stature associated with neuroradiological abnormalities and one or more additional pituitary hormone deficiencies may not need GHST. This review summarizes the current evidence on the diagnosis of GHD without stimulation tests.